A Longitudinal Multimodal Neuroimaging Study to Examine Relationships Between Resting State Glutamate and Task Related BOLD Response in Schizophrenia - Cadena, Elyse J.; White, David M.; Kraguljac, Nina V.; Reid, Meredith A.; Maximo, Jose O.; Nelson, Eric A.; Gawronski, Brian A.; Lahti, Adrienne C. (Frontiers in Psychiatry, 2018)
Previous studies have observed impairments in both brain function and neurometabolite levels in schizophrenia. In this study, we investigated the relationship between brain activity and neurochemistry in unmedicated patients with schizophrenia and if this relationship is altered following antipsychotic medication by combining proton magnetic resonance spectroscopy (1H-MRS) with functional magnetic resonance imaging (fMRI). We used single voxel MRS acquired in the bilateral dorsal anterior cingulate cortex (ACC) and fMRI during performance of a Stroop color-naming task in 22 patients with schizophrenia (SZ), initially unmedicated and after a 6-week course of risperidone, and 20 matched healthy controls (HC) twice, six weeks apart. We observed a significant decrease in ACC Glx levels in medicated SZ patients compared to HC but not compared to their unmedicated baseline. In unmedicated SZ, the relationship between ACC glutamate+glutamine (Glx)/Cr levels and the blood oxygen level-dependent (BOLD) response in regions of the salience network (SN) and posterior default mode network (DMN) was opposite than of HC. After 6 weeks, the relationship between Glx and the BOLD response was still opposite between the groups; however for both groups the direction of the relationship changed from baseline to week 6. These results suggest a mechanism whereby alterations in the relationship between cortical glutamate and BOLD response is disrupting the BOLD response in major neural networks subserving cognitive processes, potentially affecting cognition. While these relationships appear to normalize with treatment in patients, the interpretations of the results are confounded by significant group differences in Glx levels, as well as the variability of the relationship between Glx and BOLD response in HC over time, which may be driven by factors including habituation to task or scanner environment.